Vibration suppression spring clamp for pressure adjuster - CHEN LIQUN; J.D.CLIFFORD; S.M.HEATON (2012)
The invention discloses a control component for fluid flow control equipment. The control component comprises a control element, a load spring and a spring clamp, wherein the control element is movably arranged to control the flow of fluid; the load spring offsets the control element at a preset position; and the spring clamp is contacted with the load spring at a plurality of points to suppress vibration on the load spring, so that resonance is reduced and/or eliminated; the spring clamp comprises a main body plate, a first arm plate and a second arm plate, wherein the first arm plate and the second arm plate extend out of the main body plate and opposite to each other; each arm plate comprises a near end close to the main body plate, a tail end away from the main body plate and a finger part upwards extending out of the tail end; and a corner part at an intersection between the finger part and the tail end comprises a forming edge which is beneficial to connection of the load spring with the spring clamp.